Microdata Collection and Openness in the Middle East and North Africa : Introducing the MENA Microdata Access Indicator - Ekhator-Mobayode, Uche Eseosa (World Bank, Washington, DC, 2022)
This paper uses a “mystery client” approach and visits the websites of national statistical offices and international microdata libraries to assess whether foundational microdata sets for countries in the Middle East and North Africa region are collected, up to date, and made available to researchers. The focus is on population and economic censuses, price data and consumption, labor, health, and establishment surveys. Following the exercise, a new microdata access indicator that measures the degree of opennes of microdata and the ease with which microdata users can understand and navigate the websites of national statistical offices is presented. The results show that about half of the expected core data sets are being collected and that only a fraction is made available publicly. As a consequence, many summary statistics, including national accounts and welfare estimates, are outdated and of limited relevance to decision makers. Additional investments in microdata collection and publication of the data once collected are strongly advised. National statistical offices in the region should make considerable improvements to the outlook of their websites to make them more user friendly. Specifically, microdata libraries and updated survey calendars should be a standard feature of the websites to ensure easy access to available microdata.